Demystifying Masculinity: Exploring the Queer Subject and Homophobia in Fernanda Melchor’s Temporada de Huracanes (2017) - Ruz, Gerardo (2024)
According to reports from the Observatorio Nacional de Crímenes de Odio contra Personas LGBT, violence towards this community has reached alarming levels in recent years. This problem has reached fiction: Fernanda Melchor addresses this topic in her novel Temporada de huracanes (2017), where the proliferation of hate crimes becomes the central theme. This article carries out a critical study on masculinity and the queer subject, analyzing how the latter influences heterocentric behavior, revealing fissures and alternative identities concealed beneath hypermasculinity. Through a meticulous analysis of the behavior of the main characters, this work scrutinizes the silences, dissonances, and behaviors that unbalance hegemonic masculinity and at the same time, explores how homophobia is used as a tool to maintain social control, which reveals a complex social problem that queer subjects suffer.